Variación geográfica en Liolaemus ornatus Koslowsky (Sauria: iguanidae) - Pereyra, Enrique (1986)
Through an statistical analysis of simple lineal regression, the geographical variation of the latitude of the iguanid Lizard Liolaemus ornatus Koslowsky was proved. It varies from North to Couth, diminishing in number of the following characters: scales around the middle of the body in the male and female, and frontal scales in females; increasing in number the paralabials scales in contact with the right subocular and the left paralabials scales both in male and female, together with the right paralabials scales in males.